Optimising the corrosion performance of hot-rolled steel bar in concrete. (18th August 2022) - Zhou, Qinghai; Yin, Yanbin; Liu, Zhiming; Zhang, Jiongming
ABSTRACT: To optimising the corrosion resistance mechanism of hot-rolled steel bar, the effects of different tempering temperatures and high-oxygen-rich oxidation times were studied by scanning electron microscopy, X-ray diffraction, Raman spectroscopy, electrochemical and atmospheric corrosion tests. The thickness of the oxide layer of the rebar could reach 10 μm and rarely corroded after high-oxygen-rich oxidation at 850°C for 1 s, which exhibits superior corrosion resistance. The electrochemical test results showed that the I corr value after 1 s of high-oxygen-rich oxidation at 850°C was about 0.02 mA cm −2, which was 56.4% lower than that of the heated specimen at 685°C (0.045 mA cm −2 ). The results of Raman spectroscopy showed that the rust layer of the heated specimen at 685°C mainly consisted of α-Fe2 O3, γ-FeOOH and α-FeOOH, and the oxidised layer after 1 s of high-oxygen-rich oxidation at 850°C mainly consisted of α-Fe2 O3 and Fe3 O4, which maintained the original oxidised layer morphology.